Modelo de ampliación de la capacidad productiva - Kalenatic, Dusko; López Bello, César Amilcar; González Rodríguez, Leonardo José (Ingeniería, 2008)
This paper is the result of the project named "Integral models for capacity management", in which a model of strategic planning for expanding the productive capacity is presented.The structure of this model projected in the long term involves the acquisition of machines and equipment, as a function of the utility that it is not perceived due to the lack of capacity to cover the potential demand. The strategic nature of the model projects the needs of infrastructure related to the machines and equipment for the stages of a production process. Also, it takes into account the workforce requirements expressed as polyvalent labour, and it allows to calculate the space needed to install new machinery and equipment within a temporary horizon. With that horizon in mind, the impact of the desicion-making on capacity expansion is analysed and evaluated. In order to simplify the model, the assumption of all stages of the process having the same technolgy is made, although it is possible to adjust the model to account for diverse technologies in different stages of the process.